Comparing Blood Sampling Techniques in Canines: A Pilot Study Using Oclacitinib - Emily Ryman; Merilyn Dobbs; Leslie Gabor; Abishek Santhakumar; Brian Cassar; Nidhish Francis (Veterinary Sciences)
Pharmacokinetic studies are critical to assess drug absorption, distribution, metabolism, and excretion in companion animals. Blood collection methods such as direct venepuncture or indwelling catheters could influence pharmacokinetic outcomes and animal welfare. A direct comparison of drug concentrations of two blood sampling methods was investigated in this study to identify any potential differences and their impact on animal welfare. Four canines (male = 3, female = 1) were treated with Apoquel® (oclacitinib 0.4–0.6 mg/kg) and blood samples were obtained via direct venepuncture into the jugular and a cephalically placed catheter. The drug distribution and cortisol concentration were examined over several time points (0.25, 0.5, 1, 2, 4, and 6 h post treatment). Statistical analysis revealed no significant differences (p > 0.05) in the concentration of the drug between the two collection methods, indicating that both methods are acceptable in generating reliable results for pharmacokinetic data. Nevertheless, cortisol levels indicated a trend suggesting catheter collection may be associated with reduced stress compared to direct venepuncture (Catheter = 201 ± 91; Direct venepuncture = 208 ± 96. This study provides evidence to use a less invasive blood collection such as via a catheter during intensive bleeding schedules that are required in early drug development, thereby improving the overall welfare for the animal.